"You felt like a prisoner in your own self, trapped": the experiences of Aboriginal people with acquired communication disorders. Issue 13 (19th June 2021) - Armstrong, Elizabeth; Coffin, Juli; Hersh, Deborah; Katzenellenbogen, Judith M.; Thompson, Sandra C.; Ciccone, Natalie; Flicker, Leon; Woods, Deborah; Hayward, Colleen; Dowell, Catelyn; McAllister, Meaghan
Abstract: Purpose: Aboriginal Australians are under-represented in brain injury rehabilitation services despite a high incidence of both stroke and traumatic brain injury in this population. This study aimed to explore the experiences of Aboriginal Australian adults with acquired communication disorders (ACDs) after brain injury for the first time to inform the development of accessible and culturally secure service delivery models. Methods and materials: Semi-structured interviews were undertaken with 32 Aboriginal people who had experienced a brain injury resulting in ACDs (aged 35–79 years) and 18 family members/carers across Western Australia. Thematic analysis identified common themes across participants. Results: Overall themes related to communication (both related to the communication disorder and general healthcare interactions), health and social contexts, recovery, and support, being away from family and country, knowledge and beliefs about brain injury, and follow-up. Conclusions: An increase in healthcare staff's appreciation of the health and social contexts of Aboriginal people after brain injury is needed in order to improve communication with Aboriginal patients and the ability to offer accessible rehabilitation services. Ongoing support is required, with cultural identity noted as key to ensuring cultural security and ultimately recovery. Involvement of family and other Aboriginal people in recovery processes, as well as access to relevant Aboriginal languages and proximity to ancestral lands is central. Implications for rehabilitation: Acknowledgment of cultural identity and strengths through involvement of extended family and Aboriginal Hospital Liaison Officers, access to language and proximity to country all central to rehabilitation planning for Aboriginal people after brain injury. Cultural security training for rehabilitation staff is recommended focusing on clear two-way communication skills to make medical information accessible for Aboriginal patients and to listen to patients' concerns in a way that respects cultural context. Information regarding practical support and implications for ongoing management of life after brain injury (for the person and their family) is essential, and should supplement the medical-related information provided. Follow-up post discharge from hospital best facilitated through establishing contact with local Aboriginal community through Aboriginal community controlled health services, community elders, and Aboriginal health workers across organisations.